Experimental behavior based on effective slab width acting as a flange with supporting steel beams in composite floors with openings - Magdy Khalaf; Ashraf El-Shihy; El-Sayed El-Kasaby; Ahmad Youssef Civil Engineering Dept., Faculty of Engineering, Benha University, Benha, Egypt. (Fracture and Structural Integrity)
An experimental study with many variables was carried out to investigate the effective width of simply supported composite beams (T and L sec. beams) with and without slab opening. Three full-scale composite slab models with six different carrier simply supported composite beams (three with T-sec. and three with L-sec.) with constant slab rectangularity were tested. Each model was loaded by a uniform distributed load (within elastic behavior zone) then loaded by means of two-concentrated loads system acting at equal distances from supports till failure. One of them without slab opening and the others with two symmetric slab openings and constant opening position in direction parallel to main supporting beams longitudinal axes. In this research, the tested model features, materials properties and measurement instrumentations are described in brief. The maximum load carrying capacity; crack patterns, deflections at different positions and generated strains in form of estimated effective width were experimentally investigated. Interesting gained results were recorded such that more than 100% of slab effective width is preserved for interior supporting beams if the openings are away enough from carried composite slabs structural carried zones while only 70% was preserved for exterior ones. Also, concentrated loads manner reduced carried composite slab effective width to be85%in average of that recorded for equivalent distributed loads. Some conclusions and recommendations are introduced.